1996
DOI: 10.1016/0304-3959(95)00189-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between celiac plexus block and morphine treatment on quality of life in patients with pancreatic cancer pain

Abstract: Twenty-one patients with pancreatic cancer pain were studied to evaluate the effectiveness of celiac plexus block (CPB) on pain relief and quality of life (QOL), compared to the traditional NSAID-morphine treatment. The criteria were morphine consumption, visual analogue pain scale (VAS), performance status (PS) determined by medical and nursing staffs, and answers to QOL questionnaires. Morphine consumption, VAS, PS, and self-assessed QOL scores were taken when the administration of morphine was necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(193 citation statements)
references
References 16 publications
4
181
2
6
Order By: Relevance
“…A randomized placebo-controlled trial of intraoperative CPB in patients with pancreatic cancer showed lower pain scores in the treatment group throughout the follow-up [1]. Others confirmed lower pain scores after percutaneous CPB in patients not undergoing operation [2,3,4,5,6]. …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A randomized placebo-controlled trial of intraoperative CPB in patients with pancreatic cancer showed lower pain scores in the treatment group throughout the follow-up [1]. Others confirmed lower pain scores after percutaneous CPB in patients not undergoing operation [2,3,4,5,6]. …”
Section: Introductionmentioning
confidence: 94%
“…These interventions have been shown to produce substantial reductions in pain scores in uncontrolled studies [4,5,11,16]. There are no randomized data for TS, but several randomized trials of CPB have shown lower pain scores compared with MM alone [2,3,6]. The most recent [6] was also the most relevant to our study: patients had protocol-driven MM, and the trial was double blinded, by the use of a placebo injection.…”
Section: Discussionmentioning
confidence: 99%
“…Kawamata et al [ 38 ] found a delayed but signi fi cant reduction in opioid requirement 4-7 weeks after neurolysis and that consumption continued to decrease over time. Another study found that celiac plexus neurolysis caused a signi fi cant but not complete decrease in opioid consumption; patients experienced a mean reduction of 40-80 mg/day of oral morphine [ 4 ] .…”
Section: Ef Fi Cacymentioning
confidence: 97%
“…Multiple studies were unable to fi nd statistically signi fi cant differences between medically managed patients and patients who underwent neurolysis, when evaluating quality of life [ 6,34,38 ] . However, the results from Kawamata et al [ 38 ] indicate celiac plexus blockade does not directly improve quality of life in patients with pancreatic cancer pain, but it may prevent deterioration in quality of life by the long-lasting analgesic effect, limitation of side effects, and reduction of morphine consumption, compared to treatment only with NSAIDs and morphine.…”
Section: Ef Fi Cacymentioning
confidence: 97%
“…In most cases, analgesic responses are high (>50%) with a wide range of duration. 41 No controlled trials have been conducted in which conventional pain management is compared to neurolytic intervention. Complications are usually mild, but in rare cases the procedure can cause significant complications, including pneumothorax, paraplegia, and ischemic gangrene of the bowel.…”
Section: Painmentioning
confidence: 99%